Cellular behaviour of hepatocyte‐like cells from nude mouse bone marrow‐derived mesenchymal stem cells on galactosylated poly(D, L‐lactic‐co‐glycolic acid). (20th June 2013) - Roh, Hyun; Yang, Dae Hyeok; Chun, Heung Jae; Khang, Gilson
Abstract Previously, the galactosylation of poly(d, l‐lactic‐co‐glycolic acid) (PLGA) surface was accomplished by grafting allylamine (AA), using inductively coupled plasma‐assisted chemical vapour deposition (ICP‐CVD) and conjugating lactobionic acid (LA) with AA via 1‐ethyl‐3‐(3‐dimethylaminopropyl) carbodiimide and N‐hydroxysuccinimide (EDC/NHS) activation for hepatic tissue‐engineering purposes. As a continuation study, the cellular behaviour of hepatocyte‐like cells (HLCs) on the surface of the galactosylated PLGA were investigated. Nude mouse bone marrow‐derived mesenchymal stem cells (MSCs) were cultured under hepatogenic conditions and the differentiated cells were characterized by reverse‐transcription polymerase chain reaction (RT–PCR), immunofluorescence and periodic acid–Schiff (PAS) staining. Galactosylated PLGA enhanced the proliferation rate of HLCs compared to the control; HLCs on the surface of the sample became aggregated and formed spheroids after 3 days of culture. A large number of cells on the surface of the sample exhibited increased liver‐specific functional activities, such as albumin and urea secretions. In addition, multicellular spheroids in the sample strongly expressed phospholyated focal adhesion kinase (pFAK) (cell–matrix interactions), E‐cadherin (cell–cell interactions) and connexin 32 (Cox32; gap junction). Copyright © 2013 John Wiley & Sons, Ltd.